The γ-secretase complex: from structure to function - Zhang, Xian; Li, Yanfang; Xu, Huaxi; Zhang, Yun-Wu (Frontiers in Cellular Neuroscience, 2014)
One of the most critical pathological features of Alzheimer’s disease (AD) is the accumulation of β-amyloid (Aβ) peptides that form extracellular senile plaques in the brain. Aβ is derived from β-amyloid precursor protein through sequential cleavage by β- and γ-secretases. γ-secretase is a high molecular weight complex minimally composed of four components: presenilins, nicastrin, anterior pharynx defective 1, and presenilin enhancer 2. In addition to APP, γ-secretase also cleaves many other type I transmembrane protein substrates. As a crucial enzyme for Aβ production, γ-secretase is an appealing therapeutic target for AD. Here, we summarize current knowledge on the structure and function of γ-secretase, as well as recent progress in developing γ-secretase targeting drugs for AD treatment.